The genus Heliopsis (Heliantheae; Asteraceae) in Mexico and the alkamides stored in its roots - García-Chávez, Abraham; Ramírez Chávez, Enrique; Molina-Torres, Jorge (Instituto de Ecología, A.C., 2004)
The genus Heliopsis belongs to the tribe Heliantheae in the Asteraceae family. It includes 14 species, most of them endemic to Mexico. One of the species, Heliopsis longipes, is utilized in traditional medicine. The high level of alkamides in its roots has already been chemically characterized. The study of these metabolites is displayed in a comparative analysis on the presence of alkamides in six Mexican species of Heliopsis. The quantitative and qualitative analysis of the alkamides stored in roots of each species is presented. Chemotaxonomic importance of alkamides in this genus is also discussed. In this work we review and update the bibliography referring to the taxonomy of the genus.